News Visibility and Corporate Philanthropic Response: Evidence from Privately Owned Chinese Firms Following the Wenchuan Earthquake - Jia, Ming (Journal of business ethics, 2015)
Considerable interest exists regarding the media’s influence on corporate reactions, but the link between media visibility and corporate philanthropic response (CPR) is not clear. Natural disasters thus provide an environment that makes visible the general processes relevant to that link. Based on agenda-setting theory, stakeholder theory, and impression-management theory, we propose that corporations that are highly visible in the news media are more likely to engage in CPR and donate more money. We also propose that companies with reputations for irresponsibility or vulnerability strengthen that tendency. Data from Chinese firms after the Wenchuan earthquake on May 12, 2008, and the corresponding empirical results support our hypotheses. This study also shows that CPR is an active conduit for deflecting undesired reputations.